Analisis Hubungan Penggunaan LKS (Lembar Kerja Siswa) dengan Prestasi Belajar Siswa pada Mata Pelajaran SKI Kelas VII MTS Nurul Falah Batujaya Karawang - Noer, Achmed Badrul Lail; Waluyo, Kasja Eki; Nur, Tajudin (Peneliti.net, 2025)
This study aims to analyze the relationship between the use of Student Worksheets (LKS) with student learning achievement in the subject of Islamic Cultural History (SKI) in class VII MTS Nurul Falah Batujaya Karawang. Education has an important role in the development of individuals and nations. An effective learning process can trigger transformation in students, and one of the important elements in learning is the use of learning media such as LKS. LKS can facilitate the teaching and learning process, encourage student independence, and improve their engagement and learning outcomes. However, this study found that the utilization of LKS at MTS Nurul Falah is still less than optimal, which has an impact on students' low learning achievement. Using the ex post facto method and data collection techniques through interviews, literature study, and documentation, this study reveals that there is a positive relationship between the use of LKS and student learning achievement. Better implementation of the LKS is expected to improve the quality of learning and student achievement.